Characterization of a thermostable glycoside hydrolase (CMbg0408) from the hyperthermophilic archaeon Caldivirga maquilingensis IC‐167. (28th September 2016) - Letsididi, Rebaone; Hassanin, Hinawi AM; Koko, Marwa YF; Ndayishimiye, Jean B; Zhang, Tao; Jiang, Bo; Stressler, Timo; Fischer, Lutz; Mu, Wanmeng
Abstract: BACKGROUND: Hyperthermophilic archaea capable of functioning optimally at very high temperatures are a good source of unique and industrially important thermostable enzymes. RESULTS: A glycoside hydrolase family 1 β‐galactosidase gene ( Bgl B) from a hyperthermophilic archaeon Caldivirga maquilingensis IC‐167 was cloned and expressed in Escherichia coli . The recombinant enzyme (CMbg0408) displayed optimum activity at 110 °C and pH 5.0. It also retained 92% and 70% of its maximal activity at 115 and 120 °C, respectively. The enzyme was completely thermostable and active after 120 min of incubation at 80 and 90 °C. It also showed broad substrate specificity with activities of 8876 ± 185 U mg −1 for p ‐nitrophenyl‐β‐d ‐galactopyranoside, 4464 ± 172 U mg −1 for p ‐nitrophenyl‐β‐d ‐glucopyranoside, 1486 ± 68 U mg −1 for o‐nitrophenyl‐β‐d ‐galactopyranoside, 2250 ± 86 U mg −1 for o ‐nitrophenyl‐β‐d ‐xylopyranoside and 175 ± 4 U mg −1 for lactose. A catalytic efficiency ( k cat / K m ) of 3059 ± 122 mmol L −1 s −1 and K m value of 8.1 ± 0.08 mmol L −1 were displayed towards p ‐nitrophenyl‐β‐d ‐galactopyranoside. CONCLUSION: As a result of its remarkable thermostability and high activity at high temperatures, this novel β‐galactosidase may be useful for food and pharmaceutical applications. © 2016 Society of Chemical Industry